PERLINDUNGAN HUKUM TERHADAP HAK ANAK SEBAGAI PELAKU TINDAK PIDANA PENCURIAN YANG MENGGUNAKAN SENJATA TAJAM PADA TAHAP PENYIDIKAN DI POLRESTA PADANG - Mufty, Mufty; Gusman, Erry; Zulfiko, Riki (Universitas Ekasakti, 2023)
Laws are rules that allow people in general to actively carry out through special intermediaries who have the authority to carry out legal coercion, economic sanctions such as fines, etc. Children are part of the younger generation as one of the human resources who are potential and successors to the ideals of the nation's struggle in the future, who have a strategic role and have special characteristics and characteristics, require guidance and protection in order to ensure balanced physical, mental and social growth and development. Theft with violence from a legal perspective is one of the criminal acts that is troubling and detrimental to society. Therefore, legal action must be taken. The act of motorbike robbery carried out by a group of people or organized is in essence an act that is contrary to religious, moral, ethical and legal norms, and endangers the livelihoods and lives of the community, nation and state. Based on the Criminal Code, begal is included in